Client-centered occupational therapy - Law, Mary, ....- (Thorofare (N.J.) : Slack, 1998)
Contents:---------1. Client-Centered Occupational Therapy 12. Does Client-Centered Practice Make a Difference? 193. Client-Centered Practice in a changing Health Care System 294. Client-Centered Occupational Therapy: The Canadian Experience 475. The Client-Centered Occupational Therapy Process 676. Assessment in Client-Centered Occupational Therapy 897. Engaging the Person in the Process: Planning Together for Occupational Therapy Intervention 1078. Client-Centered Occupational Therapy: Collaborative Planning, Accountable Intervention 1239. Client-Centered Occupational Therapy: Ethics and Identity 145
Keywords: Ergotherapie -- Client-centered.; Ergotherapie -- Methodiek; Ergotherapie